2018
DOI: 10.1108/hff-08-2016-0300
|View full text |Cite
|
Sign up to set email alerts
|

Scrutiny of buffet mechanisms in transonic flow

Abstract: Purpose This paper aims to show results of numerical simulations of transonic flow around a supercritical airfoil at chord Reynolds number Rec = 3 × 106, with the aim of elucidating the mechanisms responsible for large-scale shock oscillations, namely, transonic buffet. Design/methodology/approach Unsteady Reynolds-averaged Navier–Stokes simulations and detached-eddy simulations provide a preliminary buffet map, while a high fidelity implicit large-eddy simulation with an upstream laminar boundary layer is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Performing a large-eddy simulation of a supercritical laminar airfoil (OALT25) at α = 4 • and M = 0.735, but at a higher Reynolds number of Re = 3 • 10 6 , Dandois et al [43] reported shock motion (a permanent back and forth moving shock wave) at significantly higher Strouhal numbers (St = 1.2) compared to typical buffet frequencies, and linked it to a breathing phenomenon of the separation bubble associated with downstream convecting vortices. Similar phenomena were reported by Memmolo et al [17] analysing the V2C airfoil at α = 7 • and high Reynolds numbers using large-eddy simulation. In a URANS parameter study exploring the buffet domain varying the angle of attack (3 ≤ α ≤ 9.5) and Mach number (0.55 < M < 0.75), an interesting coexistence between type A and type C shock motion was reported by Giannelis et al [44].…”
Section: Dynamic Mode Decompositionsupporting
confidence: 88%
See 2 more Smart Citations
“…Performing a large-eddy simulation of a supercritical laminar airfoil (OALT25) at α = 4 • and M = 0.735, but at a higher Reynolds number of Re = 3 • 10 6 , Dandois et al [43] reported shock motion (a permanent back and forth moving shock wave) at significantly higher Strouhal numbers (St = 1.2) compared to typical buffet frequencies, and linked it to a breathing phenomenon of the separation bubble associated with downstream convecting vortices. Similar phenomena were reported by Memmolo et al [17] analysing the V2C airfoil at α = 7 • and high Reynolds numbers using large-eddy simulation. In a URANS parameter study exploring the buffet domain varying the angle of attack (3 ≤ α ≤ 9.5) and Mach number (0.55 < M < 0.75), an interesting coexistence between type A and type C shock motion was reported by Giannelis et al [44].…”
Section: Dynamic Mode Decompositionsupporting
confidence: 88%
“…While high-amplitude lift fluctuations associated with buffet are typically observed at the same frequency as the back-and forth-moving shock waves, there is no obvious correlation in the present case, as upstream-propagating shock waves are generated at significantly higher frequencies (St = 0.4 − 0.7) and leave the airfoil via the leading edge. While studies of the same airfoil at M = 0.7 and significantly higher Reynolds numbers close to experimental conditions (Re = 3 • 10 6 ) do not suggest transonic buffet at α = 4 • , low-frequency oscillations at St ≈ 0.1 are observed for α > 5 • [17,20]. The latter results, comparing delayed detached-eddy simulations (DDES), implicit large-eddy simulations (ILES), and unsteady Reynolds averaged Navier-Stokes (URANS) approaches, show high sensitivity of the low-frequency buffet phenomenon to the modelling methodology applied.…”
Section: Unsteady Flow Structures At α = 4 •mentioning
confidence: 53%
See 1 more Smart Citation
“…On the numerical side, there are very few studies on the laminar transonic buffet phenomenon on airfoils. Memmolo, Bernardini & Pirozzoli (2016) have performed a large-eddy simulation of transonic buffet in laminar conditions. Two main peaks were identified: a low-frequency peak at St 0.1 concentrated around the mean shock position associated with transonic buffet; and a secondary peak at higher frequency (St 1) attributed to a Kelvin-Helmholtz (K-H) vortex shedding process in the separation.…”
Section: Introductionmentioning
confidence: 99%
“…These waves are scattered at the TE, generating new waves that travel backward outside the boundary layer up to the shock. The numerical studies of Deck [2] and Memmolo et al [3] suggest that the waves propagating downstream are hydrodynamic waves while those propagating upstream are acoustic waves. Memmolo et al describe all the possible acoustic rays displaying the right frequency, which are emitted at the TE and hit the shock front halfway of the sonic line.…”
mentioning
confidence: 98%